Analisis Perspektif Siswa SMA Negeri 2 Tanjung Jabung Barat terhadap Sport Tourism di Hutan Mangrove Pangkal Babu - Firna Yuniamanda; Ugi Nugraha; Wawan Junresti Daya (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the perspectives of students at SMA Negeri 2 Tanjung Jabung Barat regarding the development of sport tourism in the Pangkal Babu mangrove forest. The study employed a descriptive qualitative approach involving ten informants, consisting of nine students from grades X, XI, and XII and one physical education teacher. Data were obtained through semi-structured interviews and analyzed using NVivo 12 through coding and thematic analysis. The results indicate that students’ perceptions of sport tourism are more strongly shaped by direct experiences in engaging in physical activities than by conceptual understanding of the term sport tourism. Activities perceived as most relevant include tracking or walking, cycling, boating activities, fishing, and simple outbound activities. The attractiveness of the mangrove area mainly lies in its natural beauty, cool atmosphere, and the presence of wildlife. These activities provide benefits in the form of improved physical and mental health, educational value, and the development of students’ character. However, students and the teacher still highlight limitations related to facilities, safety aspects, and area management as issues that need attention. This study concludes that the Pangkal Babu mangrove forest has the potential to be developed as a sport tourism destination that supports physical education learning if it is managed in a planned and sustainable manner.